RECOMMENDATION FOR HIGH SCHOOL DETERMINATION BASED ON ACADEMIC POTENTIAL USING NAÏVE BAYES METHOD - I Komang Wiratama; Welda Welda; I Putu H Permana; Made D W Aristana; I Gede Iwan Sudipa (JIKO (Jurnal Informatika dan Komputer), 2022)
Education is an important factor in educating the nation's generation. Indonesia has a 9-year learning program that forms the basis for every student at every school level. Not infrequently, some students are confused in choosing a secondary school, so many students still make the wrong choice because they do not constantly adjust to their academic potential, only follow friends' invitations to continue to high school, as well as encouragement from parents. Thus, when they continue to school, they become less enthusiastic and do not participate optimally in learning at school. This study aims to support students in finding alternative secondary schools that follow students' academic potential and assessment attributes in research. The method in this research is Nave Bayes because it can produce high school recommendations by finding the most significant probability value of the attributes used in studying subject values, craft scores, and the value of the extracurricular areas of interest. The results of high school recommendations for students of SMP Negeri 3 Seririt can be used as an information, and based on the results of testing using the Confusion Matrix on 40 student data, the accuracy is 58.33%, the calculation precision is 75%, and the recall calculation is 43%.